1996
DOI: 10.1097/00006454-199603000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Prospective sandwich enzyme-linked immunosorbent assay for serum galactomannan: early predictive value and clinical use in invasive aspergillosis

Abstract: The detection of galactomannan at concentrations as low as 1 ng/ml can be useful for the early initiation of antifungal therapy and monitoring treatment in clinically documented lung aspergillosis. This technique coupled with chest computed tomography could help to restrict the need of invasive diagnostic procedures in fragile patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 21 publications
4
89
1
3
Order By: Relevance
“…Early detection of suspected lesions on CT might have resulted in an earlier start of antifungal treatment. As antifungal treatment has been shown to suppress circulating GM levels (Rohrlich et al, 1996) and we observed that GM-positive serum often became negative as soon as antifungals were started, the early start of treatment may have prevented detectable antigenaemia in a number of patients. With a PPV of 73% and a NPV of 82%, GM detection in serum may still have some additional value for diagnosing IPA in the individual patient in our clinical setting.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Early detection of suspected lesions on CT might have resulted in an earlier start of antifungal treatment. As antifungal treatment has been shown to suppress circulating GM levels (Rohrlich et al, 1996) and we observed that GM-positive serum often became negative as soon as antifungals were started, the early start of treatment may have prevented detectable antigenaemia in a number of patients. With a PPV of 73% and a NPV of 82%, GM detection in serum may still have some additional value for diagnosing IPA in the individual patient in our clinical setting.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, CT's were performed systematically and early in all patients with IPA, with a mean of 5AE3 CT's per patient, and starting within 4 d after onset of fever. GM detection for diagnosing IPA has been investigated in several studies (Dupont et al, 1987;Verweij et al, 1995a,b;Rohrlich et al, 1996;Maertens et al, 1999Maertens et al, , 2001Salonen et al, 2000;Siemann & Koch-Dorfler 2001;Sulahian et al, 2001). The antigen can be detected by a latex agglutination test or by a sandwich ELISA, the latter of which has shown the higher sensitivity (Verweij et al, 1995b;Sulahian et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The ELISA test using the MoAb EB-A2 has been investigated in recent years, 3,6,7,11,30 and two previous studies which compared the ELISA and the LA tests using the MoAb EB-A2, 6,7 showed the ELISA to be more sensitive (82.5-90% vs 27.5-70%), but less specific (84-81% vs 86-100%) than the LA test. Two different hypotheses might be advanced as possible causes of the lower specificity of the ELISA test: (1) a transient antigenemia induced by immunosuppressive therapy; or (2) a cross-reactivity with unidentified components in serum.…”
Section: Csamentioning
confidence: 99%
“…Galactomannan detection by the Platelia Aspergillus enzyme immunoassay (EIA) has proven to be a potentially promising tool for the early diagnosis of invasive aspergillosis. False-positive test results, however, have been reported for ϳ6 to 8% of neutropenic and hematopoietic stem cell transplant recipients, for 13% of liver transplant recipients, and for 20% of lung transplant recipients (4,5,9,10,12). Cytotoxic chemotherapeutic agents, autoreactive antibodies or paraproteins, or yet-unidentified serum components may account for the false-positive tests.…”
mentioning
confidence: 99%